EXTRACT OF Morinda lucida LEAF RESCUES HYPOGLYCAEMIC AND DYSLIPIDAEMIC CONDITIONS IN Plasmodium berghei-INFECTED MICE - Abdulkareem, Adam Olaitan; Babamale, Abdulkareem Olarewaju; Anifowoshe, Abass Toba; Opeyemi, Olufunke Adenike; Oloriegbe, Nusirat; Adamolekun, Comfort; Adetula , Samson; Ala, Adeola Adefoluke (Bulletin of Natural Sciences Research, 2022)
Increasing drug resistance is a great threat to malaria control. Therefore, a continuous investigation into alternative therapy to mitigate malaria-associated damages is important. In this study, we investigated the anti-hypoglycaemic and anti-hyperlipidaemic effects of aqueous extract of Morinda lucida leaf in Plasmodium berghei-infected mice. Twenty-five mice were randomly grouped into five: Uninfected, infected-untreated, chloroquine (20 mg/kg, per oral), and extract-treated (400 mg/kg and 800 mg/kg, respectively, per oral) groups. Fasting blood glucose was measured before parasite inoculation and after the last treatment. Blood was collected for lipid profile assay at the end of the 4-day treatment. Our results revealed that both chloroquine and the extract lowered parasite growth (p
Keywords: Malaria; Hypoglycaemia; Dyslipidaemia; Morinda lucida; Plasmodium berghei